Mobilizing participatory approaches to introduce transdisciplinary research elements when exploring the interface of commodity crop production and food security in Sub-Saharan Africa - Gasparatos, Alexandros; von Maltitz, Graham; Ahmed, Abubakari; Dompreh, Eric Brako; Jarzebski, Marcin Pawel; Saito, Osamu; Luhanga, Davies; Rigolot, Cyrille; Lozano Lazo, Denise Patricia (Frontiers in Sustainable Food Systems, 2023)
The production of commodity crops such as oil palm, sugarcane, cotton or cocoa has important ramifications for sustainability at multiple spatial and temporal scales. Food security is among the most heavily debated impacts of commodity crop production, especially in developing regions characterized by high rates of malnutrition and food insecurity such as Sub-Saharan Africa (SSA). Studies have identified diverse pathways through which commodity crop production can have positive or negative impacts on the different pillars of food security. This Methodology paper outlines how different participatory approaches can be mobilized to introduce transdisciplinarity research elements when exploring the adoption and impacts of commodity crop production, especially in developing regions such as SSA. It draws from the lessons learned during the design and implementation of five research projects that explored the food security outcomes of commodity crop production in different countries of SSA. Collectively these research projects mobilized very diverse participatory approaches such as expert interviews, Focus Group Discussions (FGDs), participatory mapping, mediated modeling, and participatory scenario analysis. Beyond being instrumental for data collection, these participatory approaches served multiple other research functions. In particular they helped (a) identify research priorities, knowledge gaps, and underlying phenomena, (b) formalize impact mechanisms and develop methodology, and (c) interpret data and validate findings. Furthermore, they contributed to the credibility and relevance of the research, and to a lesser extent to the legitimacy and effectiveness, all of which are considered important principles of transdisciplinary research. Through these diverse contributions they were instrumental in integrating valuable insights from stakeholders holding very complementary expertise in commodity crop value chains at different scales. In this sense they can act as valuable entry points to introduce transdisciplinary research elements in projects exploring the interface of food security and commodity crop value chains (or food systems more broadly), especially in contexts that truly transdisciplinary research is not feasible or desirable.